2022
DOI: 10.1136/jmg-2022-108654
|View full text |Cite
|
Sign up to set email alerts
|

TMPRSS3 expression is limited in spiral ganglion neurons: implication for successful cochlear implantation

Abstract: BackgroundIt is well established that biallelic mutations in transmembrane protease, serine 3 (TMPRSS3) cause hearing loss. Currently, there is controversy regarding the audiological outcomes after cochlear implantation (CI) for TMPRSS3-associated hearing loss. This controversy creates confusion among healthcare providers regarding the best treatment options for individuals with TMPRSS3-related hearing loss.MethodsA literature review was performed to identify all published cases of patients with TMPRSS3-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…39,58 A recent study also showed low TMPRSS3 expression in human auditory neurons. 58 By RNAscope, we found that AAV2 carrying the human TMPRSS3 coding sequence can properly target IHCs, OHCs, and SGNs. The TMPRSS3 transgene expression pattern resembles that of the WT Tmprss3 expression.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…39,58 A recent study also showed low TMPRSS3 expression in human auditory neurons. 58 By RNAscope, we found that AAV2 carrying the human TMPRSS3 coding sequence can properly target IHCs, OHCs, and SGNs. The TMPRSS3 transgene expression pattern resembles that of the WT Tmprss3 expression.…”
Section: Discussionmentioning
confidence: 95%
“…In mouse Tmprss3 has been shown to be expressed in hair cells, and other cochlear cell types including the cells in the modiolus region during development. 39,58 A recent study also showed low TMPRSS3 expression in human auditory neurons. 58 By RNAscope, we found that AAV2 carrying the human TMPRSS3 coding sequence can properly target IHCs, OHCs, and SGNs.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Two recent reports aggregated the results of published CI cases of patients with pathogenic TMPRSS3 variants. CI outcomes were variable with the majority of the studies showing "positive outcomes" (Moon et al 2021) or "favorable outcomes" (Chen et al 2022) relating to an improvement. While "positive outcomes" or "favorable outcomes" are not well defined in the literature, we have calculated quartiles for word recognition score The three quartiles (blue arrows) of cochlear implant performance are defined as the first or lower quartile (Q1; 25th percentile), the second quartile, which is also the median (Q2; 50th percentile), and the third or upper quartile (Q3; 75th percentile).…”
Section: Introductionmentioning
confidence: 99%